2021
DOI: 10.7762/cnr.2021.10.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorella vulgaris on Liver Function Biomarkers: a Systematic Review and Meta-Analysis

Abstract: This study presents a comprehensive systematic review and meta-analysis of randomized controlled trials (RCTs) on Chlorella vulgaris ( C. vulgaris ) supplementation and liver function biomarkers. Pertinent studies were identified using Scopus, ISI Web of Science, PubMed, and Cochrane library databases up to August 2020. Mean differences were pooled using a random-effects model. Pooling 7 RCTs together showed that C. vulgaris supplementation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additionally, they discovered that C. pyrenoidosa reduced lipid peroxide levels and restored normal triglyceride levels in rat serum. When compared to earlier research, the current study revealed limited impacts on cell viability; this could be because the current study utilized a low concentration 33,34 .…”
Section: Figure 3 General Biofilm Structure Before and After The Trea...contrasting
confidence: 61%
“…Additionally, they discovered that C. pyrenoidosa reduced lipid peroxide levels and restored normal triglyceride levels in rat serum. When compared to earlier research, the current study revealed limited impacts on cell viability; this could be because the current study utilized a low concentration 33,34 .…”
Section: Figure 3 General Biofilm Structure Before and After The Trea...contrasting
confidence: 61%
“…Amongst the parameters investigated in broilers’ blood, aspartate aminotransferase (AST) was significantly decreased in the CCE-fed broilers. AST reflects the condition of liver function [ 44 ]. Overlooking the cytoprotective properties of carotenoids against liver oxidative damage by restraining or delaying the oxidation and suppressing ROS production, they are also considered precursors of retinol (vit A), which is involved in hepatic stellate cells rejuvenation, thereby, preventing the progression of fibrosis to hepatocellular carcinoma in humans [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that hepatocytes are in the frontline against oxidative damage [ 45 ]. Even though growing evidence from animal and human studies suggests that C. vulgaris can be a promising hepatoprotective agent, the results are still controversial, as recently reviewed by Yarmohammadi et al [ 46 ]. Herein, none of the aminotransferases enzymes (AST and ALT) was affected by dietary inclusion of 10 % C. vulgaris , supplemented or not with both exogenous CAZymes.…”
Section: Discussionmentioning
confidence: 99%